RANCANG BANGUN PERANGKAT PENDUKUNG UNTUK PROSES PEMOTONGAN DENGAN PLASMA CUTTING - Ferry Budhi Susetyo; Ilhamullah; Calfin Aldo Maidi Frima; Anggi Kusuma; Ahmad Lubi (Universitas Negeri Jakarta, 2022)
Material cutting can use a tool commonly called plasma cutting. In general, the plasma cutting used today is still using your own hands or manually, and is not equipped with driving support equipment. This results in the performance of plasma cutting when cutting is not maximized because the movement is relatively not constant. For this reason, it will be designed, manufactured, and tested for cutting support equipment with a rectifier rail system for plasma cutting. In the process of making this supporting equipment, it also uses a threaded rod so that it can move forward and backward by using an electric motor. The design of supporting equipment for the cutting process begins with the creation of a plasma cutting design. Then design the mechanical and electrical components. Then calculate the plasma cutting torque moving forward and backward. Then proceed with the process of making the device and finally testing it. The trial step begins with turning on the compressor, and plasma inverter and preparing steel measuring 4, 6, and 10 mm. Once ready, then proceed with the process of cutting the material and cleaning the material. The results of the cut were then observed visually. The results obtained, that this plasma cutting support equipment can operate properly. The plasma cutting support equipment can cut steel plates with a thickness of 4, 6, and 10 mm very well.